Analisis Rantai Nilai pada Agroindustri di Bolu Pisang Bu Wita, Kota Bandung - Andiani, Felicia Levina; Wulandari, Eliana (Universitas Galuh, 2025)
Agroindustry, such as Bolu Pisang Bu Wita, is a processing activity that utilizes agricultural products to be transformed into value-added products and enhance competitiveness. In managing its business, the production process will involve many parties in the activities of each chain. Value chain analysis is important for business sustainability to identify activities that can create competitive advantages, thereby helping a business to improve product quality and enhance competitiveness. The research method used in this study is a qualitative method. The results show that there are four actors in the value chain, i.e., farmers, middlemen, suppliers, and Bolu Pisang Bu Wita. The value chain analysis was conducted by analyzing primary and supporting activities which each actor has different activities. Each actor in the value chain has different competitive advantages that can be used to improve the competitiveness and performance of a business. For middlemen and suppliers, they can maintain the quality of the bananas to meet consumer quality standards, thust the selling price does not decrease. For Bolu Pisang Bu Wita, they can consider business development either through packaging or presentation.